2016
DOI: 10.1002/cyto.b.21321
|View full text |Cite
|
Sign up to set email alerts
|

CD163 and CD206 expression does not correlate with tolerance and cytokine production in LPS‐tolerant human monocytes

Abstract: The effect of LPS in the expression of CD163 and CD206 on monocytes is not reverted in LPS tolerant cells, and the inhibition of inflammatory cytokines in tolerant cells is not related with modulation of these receptors. © 2016 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
2
15
2
Order By: Relevance
“…In contrast to our findings, it has been shown that CD163-positive macrophages under a double LPS stimulation paradigm display a higher intracellular content of TNF-α in comparison to their CD163-negative counterparts (Alves-Januzzi, et al, 2015). Here, we show that CD163 overexpression resulted in a reduction of released TNF-α.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, it has been shown that CD163-positive macrophages under a double LPS stimulation paradigm display a higher intracellular content of TNF-α in comparison to their CD163-negative counterparts (Alves-Januzzi, et al, 2015). Here, we show that CD163 overexpression resulted in a reduction of released TNF-α.…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, human monocytes that are tolerant to LPS present inhibited inflammatory cytokine production but retain the ability to phagocytose bacteria and to generate reactive oxygen species (45,49). In our study, CD163 and CD206 expression, markers of alternative activated macrophages (M2), did not correlate with tolerance and cytokine production in LPS-tolerant human monocytes (50).…”
Section: The Pathophysiology Behind the Conceptcontrasting
confidence: 54%
“…Contradictory results have been reported on the expression levels of CD163 on endotoxin-tolerant monocytes. While some studies suggested that upregulated CD163 on monocytes is a marker of endotoxin tolerance [ 45 ], the others found no association between expression levels and tolerant state [ 46 ]. Decreased expression of anti-inflammatory CD163 by monocytes in T2DM provides additional evidence that innate immune response in these patients is disturbed.…”
Section: Discussionmentioning
confidence: 99%